2002
DOI: 10.2466/pr0.2002.91.3.711
|View full text |Cite
|
Sign up to set email alerts
|

Environments of Physically Neglected Children

Abstract: A reanalysis of data from the Gaudin, Polansky, Kilpatrick, and Shilton 1996 study of 185 low-income families combined information from neglectful families with information from the comparison group. Physical neglect was related to maternal depression, more adult problems, stressful life events, negative family affect, and low social support. Multivariate analyses indicated that a combination of higher maternal education, positive family affect, more supportive services, and fewer stressful life events predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…All these challenges contribute to parenting stress and mental distress (Xu et al 2020). Our findings also indicate that grandparent kinship caregivers' parenting stress and mental distress are associated with elevated psychological aggression, corporal punishment, and neglect towards their grandchildren, which is in line with previous findings among biological parents (Casady and Lee 2002;Holden and Banez 1996;Lee 2013;Liu and Wang 2015;Slack et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…All these challenges contribute to parenting stress and mental distress (Xu et al 2020). Our findings also indicate that grandparent kinship caregivers' parenting stress and mental distress are associated with elevated psychological aggression, corporal punishment, and neglect towards their grandchildren, which is in line with previous findings among biological parents (Casady and Lee 2002;Holden and Banez 1996;Lee 2013;Liu and Wang 2015;Slack et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Such possibility is consistent with the emergence of more multifaceted knowledge structures. It is known that low levels of education of parents have been associated with child neglect (e.g., Casady & Lee, 2002; Coohey, 2007), which can lead us to think that this lower complexity of parental schemata is related with a general lack of cognitive functioning, and not specific to parenting cognitions. However, and despite the fact that the differences in schema complexity are associated with sociodemographic variables (e.g., Calheiros & Rodrigues, 2016; Narciso et al, 2018; Sameroff & Fiese, 1992), previous studies about the definitions of child abuse and neglect have shown that mothers are homogeneous in their conceptions about the basic elements of caregiving independently of their educational and socioeconomic level (Polansky, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in terms of sociodemographic characteristics, there were significant differences between the groups, with nonreferred mothers showing higher educational level and higher income than referred mothers, which could contribute to explain the differences observed across groups. Although a more balanced sample could help disentangling these issues in the future, the differences observed between groups may mirror the reality, to the extent that low educational (e.g., Casady & Lee, 2002; Coohey, 2007) and socioeconomic levels (e.g., Kang, 2013; Klein, 2011; Magnuson & Duncan, 2002) have been associated with child abuse and neglect cases. Furthermore, while referred mothers had children referred in the child protection system, there was no control for this variable in the nonreferred group.…”
Section: Discussionmentioning
confidence: 99%
“…Ratings were then converted into Seriousness Scores (Magura & Moses, 1986) for each module, as well as a total score, for analysis. These scales have been used to measure neglect in prior studies (Dubowitz et al, 2004) and has significantly discriminated between neglectful and comparison parents (Gaudin & Polansky, 1992; Casady & Lee, 2002). In past work, inter-rater reliability was maintained at a greater than .90 level (Dubowitz et al, 2004).…”
Section: Methodsmentioning
confidence: 99%